Clinical profile and outcome of isolated pulmonary embolism: a systematic review and meta-analysisResearch in context - Vincent ten Cate; Jürgen H. Prochaska; Andreas Schulz; Markus Nagler; Alejandro Pallares Robles; Kerstin Jurk; Thomas Koeck; Steffen Rapp; Christoph Düber; Thomas Münzel; Stavros V. Konstantinides; Philipp S. Wild (EClinicalMedicine, 2023)
Summary: Background: Isolated pulmonary embolism (PE) appears to be associated with a specific clinical profile and sequelae compared to deep vein thrombosis (DVT)-associated PE. The objective of this study was to identify clinical characteristics that discriminate both phenotypes, and to characterize their differences in clinical outcome. Methods: We performed a systematic review and meta-analysis of studies comparing PE phenotypes. A systematic search of the electronic databases PubMed and CENTRAL was conducted, from inception until January 27, 2023. Exclusion criteria were irrelevant content, inability to retrieve the article, language other than English or German, the article comprising a review or case study/series, and inappropriate study design. Data on risk factors, clinical characteristics and clinical endpoints were pooled using random-effects meta-analyses. Findings: Fifty studies with 435,768 PE patients were included. In low risk of bias studies, 30% [95% CI 19–42%, I2 = 97%] of PE were isolated. The Factor V Leiden [OR: 0.47, 95% CI 0.37–0.58, I2 = 0%] and prothrombin G20210A mutations [OR: 0.55, 95% CI 0.41–0.75, I2 = 0%] were significantly less prevalent among patients with isolated PE. Female sex [OR: 1.30, 95% CI 1.17–1.45, I2 = 79%], recent invasive surgery [OR: 1.31, 95% CI 1.23–1.41, I2 = 65%], a history of myocardial infarction [OR: 2.07, 95% CI 1.85–2.32, I2 = 0%], left-sided heart failure [OR: 1.70, 95% CI 1.37–2.10, I2 = 76%], peripheral artery disease [OR: 1.36, 95% CI 1.31–1.42, I2 = 0%] and diabetes mellitus [OR: 1.23, 95% CI 1.21–1.25, I2 = 0%] were significantly more frequently represented among isolated PE patients. In a synthesis of clinical outcome data, the risk of recurrent VTE in isolated PE was half that of DVT-associated PE [RR: 0.55, 95% CI 0.44–0.69, I2 = 0%], while the risk of arterial thrombosis was nearly 3-fold higher [RR: 2.93, 95% CI 1.43–6.02, I2 = 0%]. Interpretation: Our findings suggest that isolated PE appears to be a specific entity that may signal a long-term risk of arterial thrombosis. Randomised controlled trials are necessary to establish whether alternative treatment regimens are beneficial for this patient subgroup. Funding: None.